Immunolocalization of hordein synthesis and transport in developing barley endosperm - Gregory Tanner; Allison van deMeene; Anthony Bacic (Plant Direct)
Abstract The spatial accumulation of hordeins in the developing endosperm of barley grains was examined by immunofluorescence microscopy (immunolight microscopy [iLM]) and immunoelectron microscopy (iEM) to establish the timing and subcellular pattern of hordein synthesis and deposition. The pattern seen for hordeins was compared to other abundant grain proteins, such as serpin Z4 and lipid transfer protein 1 (LTP1). Hordein accumulates throughout grain development, from 6 to 37 days post‐anthesis (DPA). In contrast, serpin Z4 was present at 6 DPA, but the greatest synthesis and accumulation occurred during the middle of seed development, from 15 to 30 DPA. LTP1 accumulated later in seed development, from 15 to 30 DPA. Hordeins accumulated within the lumen of the endoplasmic reticulum (ER), were exocytosed from the ER membrane, and accumulated in protein bodies, which then fused either with the protein storage vacuoles or with other protein bodies, which also later fused with the protein storage vacuoles. iEM showed hordein, and LTP1 appeared not to traverse the Golgi apparatus (GA). Hordein, LTP1, and serpin Z4 colocalized to the same protein bodies and were co‐transported to the protein storage vacuole in the same protein bodies. It is likely that this represents a general transport mechanism common to storage proteins in developing grains.